Increased expression with differential subcellular location of cytidine deaminase APOBEC3G in human CD4+ T‐cell activation and dendritic cell maturation. Issue 7 (12th April 2016) - Oliva, Harold; Pacheco, Rodrigo; Martinez‐Navio, José M; Rodríguez‐García, Marta; Naranjo‐Gómez, Mar; Climent, Núria; Prado, Carolina; Gil, Cristina; Plana, Montserrat; García, Felipe; Miró, José M; Franco, Rafael; et al.
Abstract : APOBEC3G (apolipoprotein B mRNA editing enzyme catalytic polypeptide‐like 3G; A3G) is an innate defense protein showing activity against retroviruses and retrotransposons. Activated CD4 + T cells are highly permissive for HIV‐1 replication, whereas resting CD4 + T cells are refractory. Dendritic cells (DCs), especially mature DCs, are also refractory. We investigated whether these differences could be related to a differential A3G expression and/or subcellular distribution. We found that A3G mRNA and protein expression is very low in resting CD4 + T cells and immature DCs, but increases strongly following T‐cell activation and DC maturation. The Apo‐7 anti‐A3G monoclonal antibody (mAb), which was specifically developed, confirmed these differences at the protein level and disclosed that A3G is mainly cytoplasmic in resting CD4 + T cells and immature DCs. Nevertheless, A3G translocates to the nucleus in activated‐proliferating CD4 + T cells, yet remaining cytoplasmic in matured DCs, a finding confirmed by immunoblotting analysis of cytoplasmic and nuclear fractions. Apo‐7 mAb was able to immunoprecipitate endogenous A3G allowing to detect complexes with numerous proteins in activated‐proliferating but not in resting CD4 + T cells. The results show for the first time the nuclear translocation of A3G in activated‐proliferating CD4 + T cells.